2D CuO/rGO nanocomposite: a novel architecture for enhanced Cr(VI) photo-reduction - Islam Gomaa; Ahmed Helal; Medhat A. Ibrahim; Nasser Mohammed Hosny (BMC Chemistry)
Abstract The urgent need for efficient detoxification of carcinogenic hexavalent chromium (Cr(VI)) in aquatic environments has driven the development of advanced photocatalytic materials. This study presents the synthesis of 2D CuO/reduced graphene oxide (rGO) nanocomposite via probe sonication, designed to synergistically enhance the photocatalytic reduction of Cr(VI) to less toxic Cr(III). The nanocomposite was meticulously characterized using XRD, HRTEM, FESEM, XPS, and UV-Vis diffuse reflectance spectroscopy. Structural analysis confirmed the formation of CuO nanosheets (average size: 396 nm, thickness: 6 nm) integrated with rGO, where the rGO acted as an electron acceptor, mitigating charge recombination. XPS revealed Cu²⁺ in CuO and Cu(OH)₂ phases, while FTIR confirmed interfacial interactions between CuO and rGO via oxygen functional groups. The CuO/rGO composite exhibited a reduced bandgap (1.35 eV → lower with rGO incorporation) and broad visible-light absorption, critical for photocatalytic activity. Under visible light, the composite achieved a remarkable 75% Cr(VI) reduction efficiency within 180 min triple that of pure CuO (25%) with a rate constant (0.007 min⁻¹) sevenfold higher. This enhancement is attributed to rGO role in facilitating electron transfer from CuO conduction band to its LUMO, minimizing electron-hole recombination. The composite demonstrated excellent recyclability over three cycles without significant efficiency loss. These findings underscore the potential of CuO/rGO as a robust, sustainable photocatalyst for environmental.